Reseña de: Pasolini, Alessandra y Pilo, Rafaella (eds.), Cagliari and Valencia during the Baroque Age - Ciaramitaro, Fernando (Espacio Tiempo y Forma. Serie IV, Historia Moderna, 2019)
Reseña de: Pasolini, Alessandra y Pilo, Rafaella (eds.), Cagliari and Valencia during the Baroque Age. Essays on Art, History and Literature, Valencia, Albatros, 2016, 239 pp., ISBN: 9788472743311.